Evolución de la Auditoría de Sistemas en Colombia (2022)
This article aims to publicize the evolution of the audit of systems in Colombia, what was its possible beginning, its main drivers, see in which certain audit terms that are frequently used today took more strength. How the international audit environment influenced Colombia and what changes brought about the use of technology tools in different areas of the Colombian market and government